ΝΙΚΟΣ ΣΙΓΑΛΑΣ, «…Όπως όλες οι γυναίκες οι όμοιες με αυτή, όπως η Αλκμήνη…»: Γυναικεία και αντρική ομοφυλοφιλία στο έργο του Εμπειρίκου - Σιγάλας Νίκος (Σύγκριση/Comparaison/Comparison, 2022)
“… as all the women like her, as Alcmene…”: Female and male homosexuality in Embiricos’ work This article deals with the place of homosexuality in Andreas Embiricos’ erotographic work. I do not argue that homosexuality holds a central place in his work. I consider, however, that it is a topic of great importance for Embiricos, for it has been a form of Eros cruelly subjected to prohibitions, stigmatisation and social outcry. Therefore, the way homosexual intercourses take place within the large spectrum of erotic interactions that constitute Embiricos’ erotography says a lot about its theoretical foundations. I believe that Embiricos’ approach to homosexuality unlocks in the most direct way his understanding of eros.